Engineering computation with Matlab - Smith, David M. (Boston, Massachusetts : Pearson, 2013)
This textbook is ideal for MATLAB/Introduction to Programming courses in both Engineering and Computer Science departments. Engineering Computation with MATLAB introduces the power of computing to engineering students who have no programming experience. The book places the fundamental tenets of computer programming into the context of MATLAB, employing hands-on exercises, examples from the engineering industry, and a variety of core tools to increase programming proficiency and capability. With this knowledge, students are prepared to adapt learned concepts to other programming languages
Chapter 1 Introduction to Computers and Programming -- 1.1 Background -- 1.2 History of Computer Architectures -- 1.2.1 Babbage's Difference Engine -- 1.2.2 Colossus -- 1.2.3 The von Neumann Architecture -- 1.3 Computing Systems Today -- 1.3.1 Computer Hardware -- 1.3.2 Computer Memory -- 1.3.3 Computer Software -- 1.3.4 Running a Computer Program -- 1.4 Running an Interpreted Program -- 1.5 Anticipated Outcomes -- 1.5.1 Introduction to MATLAB -- 1.5.2 Learning Programming Concepts -- 1.5.3 Problem-Solving Skills -- Chapter 2 Getting Started 2.1 Programming Language Background -- 2.1.1 Abstraction -- 2.1.2 Algorithms -- 2.1.3 Programming Paradigms -- 2.2 Basic Data Manipulation -- 2.2.1 Starting and Stopping MATLAB -- 2.2.2 Assigning Values to Variables -- 2.2.3 Data Typing -- 2.2.4 Classes and Objects -- 2.3 MATLAB User Interface -- 2.3.1 Command Window -- 2.3.2 Command History -- 2.3.3 Workspace Window -- 2.3.4 Current Directory Window -- 2.3.5 Variable Editor -- 2.3.6 Figure Window -- 2.3.7 Editor Window -- 2.4 Scripts -- 2.4.1 Text Files -- 2.4.2 Creating Scripts -- 2.4.3 The Current Directory -- 2.4.4 Running Scripts 2.4.5 Punctuating Scripts -- 2.4.6 Debugging Scripts -- 2.5 Engineering Example-Spacecraft Launch -- Chapter 3 Vectors and Arrays -- 3.1 Concept: Using Built-in Functions -- 3.2 Concept: Data Collections -- 3.2.1 Data Abstraction -- 3.2.2 Homogeneous Collection -- 3.3 Vectors -- 3.3.1 Creating a Vector -- 3.3.2 Size of a Vector -- 3.3.3 Indexing a Vector -- 3.3.4 Shortening a Vector -- 3.3.5 Operating on Vectors -- 3.4 Engineering Example-Forces and Moments -- 3.5 Arrays -- 3.5.1 Properties of an Array -- 3.5.2 Creating an Array -- 3.5.3 Accessing Elements of an Array 3.5.4 Removing Elements of an Array -- 3.5.5 Operating on Arrays -- 3.6 Engineering Example-Computing Soil Volume -- Chapter 4 Execution Control -- 4.1 Concept: Code Blocks -- 4.2 Conditional Execution in General -- 4.3 if Statements -- 4.3.1 General Template -- 4.3.2 MATLAB Implementation -- 4.3.3 Important Ideas -- 4.4 switch Statements -- 4.4.1 General Template -- 4.4.2 MATLAB Implementation -- 4.5 Iteration in General -- 4.6 for Loops -- 4.6.1 General for Loop Template -- 4.6.2 MATLAB Implementation -- 4.6.3 Indexing Implementation -- 4.6.4 Breaking out of a for Loop -- 4.7 while Loops 4.7.1 General while Template -- 4.7.2 MATLAB while Loop Implementation -- 4.7.3 Loop-and-a-Half Implementation -- 4.7.4 Breaking a while Loop -- 4.8 Engineering Example-Computing Liquid Levels -- Chapter 5 Functions -- 5.1 Concepts: Abstraction and Encapsulation -- 5.2 Black Box View of a Function -- 5.3 MATLAB Implementation -- 5.3.1 General Template -- 5.3.2 Function Definition -- 5.3.3 Storing and Using Functions -- 5.3.4 Calling Functions -- 5.3.5 Variable Numbers of Parameters -- 5.3.6 Returning Multiple Results -- 5.3.7 Auxiliary Local Functions -- 5.3.8 Encapsulation in MATLAB Functions
Includes index.
Keywords: ENGINEERING MATHEMATICS -- DATA PROCESSING